Upaya Meningkatkan Minat Belajar Peserta Didik melalui Penggunaan Media Wordwall di Kelas IV SDN Model Mataram Tahun Ajaran 2024/2025 - Taufik, Muhammad; Nisa, Khairun; Supriatin, Dwi (Mataram University, 2025)
The purpose of this study was to determine the significance of the improvement in students’ learning interest through the use of Wordwall media in Grade IV of SDN Model Mataram. The focus of this research was to enhance students’ learning interest in classroom activities. This study employed a Classroom Action Research (CAR) approach based on Kurt Lewin’s model. The subjects of the study were 18 fourth-grade students of SDN Model Mataram. Data were collected through observation, questionnaires, and documentation techniques. The results indicated that the use of Wordwall media effectively increased students’ learning interest. This finding was evidenced by a gradual improvement in students’ questionnaire scores across each cycle, with an average pre-action (initial test) score of 72.21, increasing to 81.18 in the post-test of Cycle I, and reaching 89.28% in Cycle II. These results demonstrate that the use of Wordwall media is highly effective in enhancing students’ learning interest in Grade IV of SDN Model Mataram.